Soft and transparent triboelectric nanogenerator based E-skin for wearable energy harvesting and pressure sensing. (2nd July 2021) - Park, Jiwon; Kim, Daeun; Kim, Youn Tae
Abstract: The demand for wearable sensor technologies has increased with the recent increase interactions humans–electronic device interactions. However, the supplying power for wearable sensors, such as E-skin and flexible electronics, remains a major technical challenge. Herein, we report a triboelectric nanogenerator (TENG)-based E-skin capable of biomechanical energy harvesting and self-pressure sensing without an external power source. PTFE-molded micro-patterned PDMS and a conductive yarn were combined to implement an E-skin with flexibility, elasticity, high sensitivity, and excellent stability. The manufactured E-skin generates a power of 154 mW m −2 for an external force of 1 kgf and exhibits stable characteristics without deterioration of output even under 4500 cycles of repeated pressure. The E-skin can charge a capacitor and drive an electronic watch as well as monitor physiological signals, such as arterial pulses. The method used in this study can be extended to potential applications for power supply in wearable/soft electronics, medical monitoring, and human–machine interfaces.